Pengaruh Customer Experience, Personalization, Customer Engagement Dan Online Customer Review Terhadap Loyalitas Pelanggan Kosmetik Wardah (Studi Kasus Pengguna Tiktok di Kota Malang) - Wulandari, Cahya; Rizal, Mohammad; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The study seeks to examine the effect of Customer Experience, Personalization, Customer Engagement, and Online Customer Review on customer loyalty of Wardah cosmetics in Malang City. The study method use quantitative approach purposive sampling, resulting in 100 respondents who are TikTok users. The data collected were analyzed through linear regression, and hypothesis test performed through F and t test. The findings indicate that, simultaneously, Customer Experience, Personalization, Customer Engagement, and Online Customer Review significantly influence customer loyalty. Partially, each of these independent variables also has a significant impact on customer loyalty to Wardah cosmetics. These results suggest that a positive customer experience, personalized services, strong customer engagement, and favorable online customer reviews can enhance customer loyalty.. Keywords: Customer Experience, Personalization, Customer Engagement, Online Customer Review, Customer Loyalty.